2018
DOI: 10.1021/acs.joc.8b00592
|View full text |Cite
|
Sign up to set email alerts
|

Buchwald–Hartwig Amination of Phosphinines and the Effect of Amine Substituents on Optoelectronic Properties of the Resulting Coupling Products

Abstract: The Buchwald-Hartwig amination of a phosphinine bearing a bromophenyl moiety was carried out using a dinuclear Ni catalyst. A variety of monoarylamines, diarylamines, and alkylamine, as well as heterocycles, were successfully converted into novel phosphinines bearing amine units. The photophysical properties of these novel phosphinines were examined, including the substituent-dependent absorption/emission features and intramolecular charge-transfer interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Nagahora et al introduced diarylamine and arylamine through the BHA reaction of 4-haloaryl-phosphinine to expand the π-electron system and revealed that the desired coupling product could be obtained only when complex 8 b (7-Br + PPh 3 ) was used (Scheme 17). [53] They attempted reactions with various catalyst systems, involving Pd and Ni; these were unsuccessful. The product aminated phosphinine derivatives emitted strong fluorescence, owing to intramolecular charge-transfer interactions.…”
Section: Activity Of Nhcà Ni(i) In Catalytic Cross-couplingmentioning
confidence: 99%
“…Nagahora et al introduced diarylamine and arylamine through the BHA reaction of 4-haloaryl-phosphinine to expand the π-electron system and revealed that the desired coupling product could be obtained only when complex 8 b (7-Br + PPh 3 ) was used (Scheme 17). [53] They attempted reactions with various catalyst systems, involving Pd and Ni; these were unsuccessful. The product aminated phosphinine derivatives emitted strong fluorescence, owing to intramolecular charge-transfer interactions.…”
Section: Activity Of Nhcà Ni(i) In Catalytic Cross-couplingmentioning
confidence: 99%
“… 56 The development of other luminescent materials featuring σ 2 ,λ 3 -phosphorus is rapidly expanding, as recent examples G–J illustrate in Chart 1 . 57 …”
Section: Introductionmentioning
confidence: 99%
“…Buchwald–Hartwig C–N cross‐coupling reaction has received much attention due to its versatility in the synthesis of a large variety of organic compounds and total synthesis of natural products . Aryl amines are synthesized via amination of aryl halides, heteroaryl halides, alkenyl halides, sulfonates, and phosphinines . Aromatic amines show biological activities and use in medicine and pharmaceutical (antibiotics and antitumors such as lobatamides and oximidines) , besides other applications in agricultural pesticides, dyes, pigments, synthetic rubber , and optoelectro‐active and photo‐active materials.…”
Section: Introductionmentioning
confidence: 99%